Afterglow of Argon Plasmas with H2, O2, N2, and CO2 Admixtures Observed by Thomson Scattering. Issue 5 (19th March 2014) - Hübner, Simon; Carbone, Emile; Palomares, Jose Maria; van der Mullen, Joost
<x xml:space="preserve">Abstract</x> This study assess the decay of a power‐pulsed microwave plasma in argon mixtures using time resolved Thomson scattering. In argon at intermediate pressure, i.e. tens of mbar, the electron temperature decays very fast after power off and approaches the heavy particle temperature, while the electron density decays slower, in the order of tens of microseconds. Argon with small admixtures of O2 or H2 exhibits a similar behavior. However, strikingly different is the result for small additions of N2 or CO2. For up to 100 μs after the power is switched off, the electron temperature does not decrease to the gas temperature but remains at values as high as 0.8 eV. Nitrogen and carbon dioxide exhibit relatively large cross‐sections to excite vibrational states by electron collisions. Knowing that, the observed post‐heating can be attributed to super‐elastic energy transfer from vibrational excited N2(X) and CO2(X) molecules to electrons.<inline-graphic xlink:href="ark:/27927/pgg5nqc4fwj" content-type="ppap201300190-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />